Cryptosporidiosis in immunocompromised children - Menon, B.S; Singh, Balbir (1999)
ln this prospective study, we examined stool specimens from children with cancer on chemotherapy who were adntitted for fever to the Universiti Sains Malaysia Hospital in Kota Baru, Kelantan. Stool specimens were examined for ova and cysts of parasites.Over a period of 15 months, there were 129 febrile episodes in 50 children with cancer and 237 stool specimens were examined. Sixty-six per cent of febrile episodes were associated with neutropenia and 9% were associated with diarrhoea. Stool parasites were found in 42% of children. The most common were helminths, followed by protozoa. Trichuristrichuri was the most common parasite (24%), followed by Ascaris lwnbricoides (22%). Hookworm was found in 2%. Giardia Iamblia was found in 6% of children, Blastocystis hominis in 4% and Cryptosporidium parvum in 2%.